SN 2023emq: A Flash-ionized Ibn Supernova with Possible C iii Emission - Pursiainen M; Leloudas G; Schulze S; Charalampopoulos P; Angus CR; Anderson JP; Bauer F; Chen TW; Galbany L; Gromadzki M; Gutierrez CP; Inserra C; et al. (IOP Publishing Ltd, 2025)
SN 2023emq is a fast-evolving transient initially classified as a rare Type Icn supernova (SN), interacting with a H- and He-free circumstellar medium (CSM) around maximum light. Subsequent spectroscopy revealed the unambiguous emergence of narrow He lines, confidently placing SN 2023emq in the more common Type Ibn class. Photometrically, SN 2023emq has several uncommon properties regardless of its class, including its extreme initial decay (faster than >90% of Type Ibn/Icn SNe) and sharp transition in the decline rate from 0.20 to 0.07 mag day(-1) at +20 days. The bolometric light curve can be modeled as CSM interaction with 0.32M(circle dot) of ejecta and 0.12M(circle dot) of CSM, with 0.006M(circle dot) of nickel, as expected of fast, interacting SNe. Furthermore, broadband polarimetry at +8.7 days (P = 0.55% +/- 0.30%) is consistent with spherical symmetry. A discovery of a transitional Type Icn/Ibn SN would be unprecedented and would give valuable insights into the nature of mass loss suffered by the progenitor just before death, but we favor an interpretation that SN 2023emq is a Type Ibn SN that exhibited flash-ionized features in the earliest spectrum, as the features are not an exact match with other Type Icn SNe to date. However, the feature at 5700 & Aring;, in the region of C iii and N ii emission, is significantly stronger in SN 2023emq than in the few other flash-ionized Type Ibn SNe, and if it is related to C iii, it possibly implies a continuum of properties between the two classes.